Hydroxycitric Acid Inhibits Renal Calcium Oxalate Deposition by Reducing Oxidative Stress and Inflammation - Liu, Xiao; Yuan, Peng; Sun, Xifeng; Chen, Zhiqiang (Current Molecular Medicine, 2020)
Objective: The study aimed to evaluate the preventive effects of hydroxycitric acid(HCA) for stone formation in the glyoxylate-induced mouse model. Materials and Methods: Male C57BL/6J mice were divided into a control group, glyoxylate(GOX) 100 mg/kg group, a GOX+HCA 100 mg/kg group, and a GOX+HCA 200 mg/kg group. Blood samples and kidney samples were collected on the eighth day of the experiment. We used Pizzolato staining and a polarized light microscope to examine crystal formation and evaluated oxidative stress via the levels of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px). Quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) was used to detect the expression of monocyte chemotactic protein-1(MCP-1), nuclear factor-kappa B (NF Κ B), interleukin-1 β (IL-1 β) and interleukin-6 (IL-6) messenger RNA (mRNA). The expression of osteopontin (OPN) and a cluster of differentiation-44(CD44) were detected by immunohistochemistry and qRT-PCR. In addition, periodic acid Schiff (PAS) staining and TUNEL assay were used to evaluate renal tubular injury and apoptosis. Results: HCA treatment could reduce markers of renal impairment (Blood Urea Nitrogen and serum creatinine). There was significantly less calcium oxalate crystal deposition in mice treated with HCA. Calcium oxalate crystals induced the production of reactive oxygen species and reduced the activity of antioxidant defense enzymes. HCA attenuated oxidative stress induced by calcium oxalate crystallization. HCA had inhibitory effects on calcium oxalate-induced inflammatory cytokines, such as MCP-1, IL- 1 β, and IL-6. In addition, HCA alleviated tubular injury and apoptosis caused by calcium oxalate crystals. Conclusion: HCA inhibits renal injury and calcium oxalate crystal deposition in the glyoxylate-induced mouse model through antioxidation and anti-inflammation.
Keywords: kidney crystallization